Introduction of SOFC Technology into Cuban Energy Sector: Technical and Sustainability Analysis - Yannay Casas Ledón; Luis E. Arteaga Pérez; Karel Dieguez Santana; Elena Rosa Domínguez; Mayra C. Morales Pérez (Journal of Chemical Engineering Research Updates, 2015)
The feasibility of integrating a solid oxide fuel cell (SOFC) technology into the Cuban energy sector is analyzed. In this context, two scenarios for power generation are assessed: the first (existing) combines a bagasse cogeneration unit and diesel combustion engines and for the second (future), diesel engines are replaced by a SOFC feed with ethanol and integrated into the sugar factory. The environmental impact (greenhouse gases), exergy efficiency, and a renewability parameter are considered as indicators for the assessment of the studied scenarios through a multifunctional unit (9.86t/h sugar, 2.195t/h of hydrated ethanol (96% w/w) and 847kWh of electricity) approach. The SOFC scenario shows significant advantages from an environmental point of view, obtaining a reduction of 55% greenhouse emissions and 60% fossil fuel consumption. At the same time, the overall process efficiency (38%) and renewability index (0.93) are higher than for the existing scenario. Furthermore, health impacts and their corresponding external cost related to airborne emissions (primary and secondary pollutant) are estimated applying the Uniform World Model (UWM). In this sense, the results show that the use of a SOFC technology involves a reduction of health impacts in 25.76 YOLL yr-1 (12%) and external costs of 52175 US$ yr-1 (12%). The potentiality of SOFC technology implementation into Cuban energy sector is assessed using a Strengths, Weaknesses, Opportunities and Threats (SWOT) approach. Nowadays, the main threat of implementation of this technology is associated to competitive energy market.